Investigating the Relationship between Burnout and Academic Self-Efficacy in EFL Learning among the Non-English Department Students in Indonesia - Lemmuela Alvita Kurniawati; Prisca Eirene Pricillia Mustafa (Intensive Journal, 2025)
Learning English as a second language (L2) can pose psychological challenges for non-English Department students, potentially affecting their motivation, emotional well-being, and academic performance. This study investigates the relationship between burnout and academic self-efficacy among non-English Department students in Indonesia. The study aims to identify students’ levels of burnout in English learning, examine their level of academic self-efficacy, and explore the relationship between the two variables. A quantitative research design was employed, involving 121 non-English Department students from 38 universities in Indonesia. Data were collected using a self-report questionnaire measuring burnout and academic self-efficacy, and were analyzed using descriptive statistics and Pearson correlation. The findings indicate that students generally experienced low levels of burnout and relatively high levels of academic self-efficacy in learning English. In addition, the results reveal a significant negative correlation between burnout and self-efficacy (r = -.659, p < .001), suggesting that students with higher self-efficacy tend to experience lower burnout. These findings highlight the vital role of self-efficacy in supporting learners’ motivation, emotional resilience, and sustained engagement in L2 learning. Pedagogically, this study suggests that English teachers and educational institutions should place greater emphasis on strengthening learners’ self-belief and confidence as a strategy to reduce burnout and improve learning outcomes among non-English Department students.